Psychological analysis and strategies for college students’ “slow employment” in the context of smart education - Zhai Yanan; Cao Jianqiao (ITM Web of Conferences, 2025)
Against the backdrop of the deep integration of smart education, the innovation of information management technology, and the rapid development of the digital society, the phenomenon of college students' “slow employment” has taken on new characteristics. Based on empirical data, this paper analyzes the psychological causes of college students' slow employment and proposes intervention strategies by combining smart education platforms, information management systems, and digital social resources. The study finds that unclear career planning, employment expectation deviation, insufficient stress resistance, and social environmental influences are the core psychological factors of slow employment, and there are significant differences in the forms of slow employment among different groups. By constructing an intervention system of "precise assessment-intelligent matching-digital empowerment," this research provides theoretical and practical references for improving the employment decision-making efficiency of college students and promoting a virtuous connection between education and the labor market.